Coupling effect of the equatorial F region irregularities on the low latitude E region instability processes - Patra, A.K.; Sripathi, S.; Tiwari, D. (My University, 2004)
[1] Simultaneous observations of E and F region irregularities made using the Gadanki MST radar are presented. The observations show that the E region echoes weaken or disappear during the growth phase of the topside F region irregularities. Unlike Jicamarca observations, no valley region echoes are observed during this phase. It is shown that the weakening or disappearance of E region signals are not directly coupled with the F region irregularities just overhead, but linked with the instability processes over the magnetic equator through the magnetic field lines. It is proposed that the fringe fields present in the valley region in association with the equatorial F region plasma bubbles, in the presence of appropriate background electric field conditions, are responsible candidates. It is shown that these fringe fields and the electric fields associated with the irregularities in the valley region can map to the low latitude E region and thereby inhibit the growth of the E region instability processes as revealed by the Gadanki radar observations.
Keywords: F region irregularitie; E region irregularitie; Electric fields; Gadanki radar observations